The Effect of Product Quality, Price, And Promotion on Consumer Satisfaction at SKJ Garage Bandar Lampung - Wijaya, Kenny; Ni Putu Widhia Rahayu (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study aims to investigate and analyze consumer satisfaction at SKJ Garage, which is influenced by independent variables, namely product quality as X1, price as X2, and promotion as X3, both partially and simultaneously. The methodology used is quantitative research. There are 144 SKJ Garage consumers in 2023. Slovin is a calculation used to determine the sample in this study, and 106 respondents were found to be in the sample. The questionnaire in the form of a Form or online is the primary data source in the study. Gform 30 respondents, showed a validity test and a reliability test, and continued with multiple linear regression testing on SPSS 25, for all answers of the research sample. The results of this study, namely, consumer satisfaction at SKJ Garage, showed that it was influenced by independent variables, namely product quality as X1, price as X2, and promotion as X3, both partially and simultaneously.